Digital Silk Road and Cross-border Payment Integration between Malaysia and China: Policy Synergies, Frictions, and Impacts on SME Transaction Costs - Anran Qiao; Bee Wah Tan; Mingpey Lu (PT FORMOSA CENDEKIA GLOBAL, 2026)
This paper examines policy synergies and frictions in Malaysia–China cross-border digital payment integration under the Digital Silk Road. Using document-based policy comparison and a structured literature review, it maps three SME cost-reduction channels—lower search and verification costs, faster clearing and settlement, and improved foreign-exchange transparency—against three governance pillars: data rules, settlement arrangements, and technical standards. The analysis finds that Malaysia’s domestic payment readiness has advanced faster than bilateral institutional coordination, creating an “integration gap” that sustains fees, delays, and compliance burdens for SMEs. Policy options include a bilateral regulatory sandbox, harmonised cross-border QR standards, and phased central-bank cooperation on atomic settlement and CBDC-related pilots.